Insertion of circularly permuted cyan fluorescent protein into the ligand-binding domain of inositol 1, 4, 5-trisphosphate receptor for enhanced FRET upon binding of fluorescent ligand. (December 2022) - Jahan, Azmeree; Akter, MST Tahmina; Takemoto, Kiwamu; Oura, Tai; Shitara, Akiko; Semba, Shingo; Nezu, Akihiro; Suto, Satoshi; Nagai, Takeharu; Tanimura, Akihiko
Highlights: Circularly permuted CFPs (cpCs) were inserted into the loop between the second and third α-helices of the ligand binding domain of IP3 receptor. Two of the fluorescent ligand-binding proteins showed correct localization and exhibited FRET upon binding of the high-affinity ligand fluorescent adenophostin A (F-ADA) and the fluorescent low-affinity ligand (F-LL). The effect of F-LL on the decrease in fluorescence ratio was reversed upon addition of IP3 by competing with IP3 . Abstract: Binding of fluorescent ligand (FL) to the cyan fluorescent protein (CFP)-coupled ligand-binding domain of the inositol 1, 4, 5-trisphosphate (IP3 ) receptor (CFP-LBP) produces fluorescence (Förster) resonance energy transfer (FRET). A competitive fluorescent ligand assay (CFLA), using the FRET signal from competition between FLs and IP3, can measure IP3 concentration. The FRET signal should be enhanced by attaching a FRET donor to an appropriate position. Herein, we inserted five different circularly permuted CFPs in the loop between the second and third α-helices to generate membrane-targeted fluorescent ligand-binding proteins (LBPs). Two such proteins, LBP-cpC157 and LBP-cpC173, localized at the plasma membrane, displayed FRET upon binding the high-affinity ligand fluorescent adenophostin A (F-ADA), and exhibited a decreased fluorescence emission ratio (480 nm / 535 nm) by 1.6- to 1.8-fold that of CFP-LBP. In addition, binding of a fluorescent low-affinity ligand (F-LL) also reduced the fluorescence ratio in a concentration-dependent manner, with EC50 values for LBP-cpC157 and LBP-cpC173 of 34.7 nM and 27.6 nM, respectively. These values are comparable to that with CFP-LBP (29.2 nM), indicating that insertion of cpC157 and cpC173 did not disrupt LBP structure and function. The effect of 100 nM F-LL on the decrease in fluorescence ratio was reversed upon addition of IP3, indicating binding competition between F-LL and IP3 . We also constructed cytoplasmic fluorescent proteins cyLBP-cpC157 and cyLBP-cpC173, and bound them to DYK beads for imaging analyses. Application of F-ADA decreased the fluorescence ratio of the beads from the periphery to the center over 3 − 5 min. Application of F-LL also decreased the fluorescence ratio of cyLBP-cpC157 and cyLBP-cpC173 by 20−25%, and subsequent addition of IP3 recovered the fluorescence ratio in a concentration-dependent manner. The EC50 value and Hill coefficient obtained by curve fitting against the IP3 -dependent recovery of fluorescence ratio can be used to estimate the IP3 concentration. Graphical abstract: Image, graphical abstract